Assessing the respiratory toxicity of dihydroxyacetone using an in vitro human airway epithelial tissue model. (September 2019) - Wang, Yiying; Wu, Qiangen; Muskhelishvili, Levan; Davis, Kelly; Bryant, Matthew; Cao, Xuefei
Abstract: Dihydroxyacetone (DHA) is an approved color additive used in sunless tanning lotions. Recently, there has been an increased use of DHA in sunless tanning booths in a manner that could result in its inhalation during application. In the present study, we have evaluated the potential for DHA causing toxicity via inhalation using a human air-liquid-interface (ALI) in vitro airway epithelial tissue model. ALI airway models have a close structural and functional resemblance to the in vivo airway epithelium, and thus data generated in these models may have relevance for predicting human responses. To simulate in vivo exposure conditions, we employed a method for liquid aerosol generation that mimics the physical form of inhaled chemicals and used doses of DHA and an exposure frequency reflecting human respiratory exposures during tanning sessions. Compared to the vehicle control, cilia beating frequency (CBF) and MUC5AC secretion were significantly decreased after each exposure. However, time-course studies indicated that both CBF and MUC5AC secretion returned to normal levels within 3 days after the treatment. Matrix metalloproteinase (MMP) release, on the other hand, was decreased 24 h after the first exposure and its level returned to baseline after 5 exposures. No significant morphological changes occurred in the DHA-treated cultures after 5 weekly exposures. Our findings indicate that DHA, at concentrations likely to be experienced by humans, has transient toxic effects on human airway ALI cultures. Highlights: Exposure to DHA aerosols results in perturbation of cilia beating frequency (CBF) and MUC5AC secretion. Changes in CBF and MUC5AC secretion are reversed to baseline level within 72 h after the exposure. MMP secretion is decreased 24 h after the first exposure. Morphology of the cultures is not affected after 5 weekly exposures. DHA aerosols have transient toxic effects on the ALI cultures under exposure conditions experienced by humans.